Ongoing Enhancement of ESL Education Through Reflective Surveys for University Students - Chugai, Оksana; Lytovchenko, Iryna (Educological discourse, 2024)
Reflective surveys in global best practices are used to ensure that the course meets the varied linguistic needs of university students. Therefore, we aimed to analyze quantitative and qualitative data on university students’ feedback across various dimensions of ESL courses and provide recommendations aimed at improving and sustaining the quality of teaching English at the university level. To achieve this, we used a mixed-method research design to obtain quantitative and qualitative data which revealed that university students expressed their overall satisfaction with the ESL courses. They especially appreciated the possibility of completing assignments asynchronously, as well as relaxed deadlines and discussions. They suggested creating study groups according to language proficiency levels and making them smaller to ensure an individual approach. The results of the research showed that students were mostly positive regarding ESL course content, teaching methods, instructor approach, assignments and assessments, class participation, technology integration, group work, resources and materials, time management, English proficiency, collaborative learning, and relevance to future careers. We observed statistically that students were especially enthusiastic about their teachers’ support and guidance, as well as about relaxed deadlines. This study highlighted the importance for students to communicate with each other in groups, play games, have discussions, do problem-solving tasks, focus on their professional needs, establish rapport with their teachers, get regular feedback and error correction. In conclusion, the study contributes to the importance of reflective surveys in holistically evaluating and refining the ESL learning experience for university students. In future research, reflective surveys could be used for teachers and students from several higher education institutions to further enrich our knowledge in this area.